Analysis and evaluation of the associativity of the communities on the map of influence of the peruvian mining industry through forward-looking tools - case Ilabaya - Inche Mitma, Jorge Luis (2013)
This paper shows the results of a research work that studied the problems that emerged in the towns inside the mining enterprises action. Likewise looked for presenting solutions by SNIP projects with purpose or revert the problems mentioned. In order to achieving the results of this work, it have to applied some prospective techniques in consults to experts, previously adapted to the scenario of the research as well as its character.